2014
DOI: 10.1128/genomea.00793-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Nonlabens ulvanivorans, an Ulvan-Degrading Bacterium

Abstract: Here we report the draft genome sequence of the bacterium Nonlabens ulvanivorans, which was recently isolated. To our knowledge, this is the first published genome of a characterized ulvan-degrading bacterium. Revealing the ulvan utilization pathways may provide access to a vast marine biomass source that has yet to be exploited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…LTR, and Pseudoalteromonas sp. PLSV, (8,12,13). Genome annotation was manually confirmed by CAZy 4 and revealed that these strains encoded many polysaccharide-degrading enzymes.…”
Section: Table 2 Primers Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…LTR, and Pseudoalteromonas sp. PLSV, (8,12,13). Genome annotation was manually confirmed by CAZy 4 and revealed that these strains encoded many polysaccharide-degrading enzymes.…”
Section: Table 2 Primers Used In This Studymentioning
confidence: 99%
“…More recently, several bacterial strains capable of metabolizing ulvan were isolated from the feces of a sea slug, Aplysia punctate, fed with Ulva. In this way, the Gram-negative Nonlabens ulvanivorans PLR was identified (6,7) and its genome was sequenced (8). A novel ulvan lyase was purified from N. ulvanivorans batch culture, sequenced, and heterologously overexpressed in Escherichia coli, and the enzyme's ability to depolymerize ulvan biochemically characterized (9).…”
mentioning
confidence: 99%
“…For example, the protein found in the bacterium Nonlabens ulvanivorans, combines two catalytic modules, one attributed to a sulfatase, and the other to a glycoside hydrolase belonging to family GH78 (rhamnosidases). This organization reflects a genomic rearrangement adapted to the degradation of ulvan, the sulfated cell-wall matrix polysaccharide found in green algae of the genera Ulva and Enteromorpha (Kopel et al, 2014). Ulvan, composed of 3O-sulfate-rhamnose, is likely more efficiently degraded by a bi-modular protein.…”
Section: Modular Sulfatasesmentioning
confidence: 99%
“…(B) Ulva degradation PUL observed in Nonlabens ulvanivorans isolated from the feces of Aplysia sp. (Kopel et al, 2014). (C) Carrageenan PUL in Cellulophaga algicola.…”
Section: Biochemically Characterized Marine Polysaccharide Sulfatasesmentioning
confidence: 99%
“…Marine bacteria producing enzymes able to degrade ulvan polysaccharides were only recently discovered (10) and the first ulvan lyase from Nonlabens (Persicivirga) ulvanivorans strain PLR was biochemically characterized as an endolytic ulvan lyase (11). The genome of N. ulvanivorans was recently sequenced (12), followed by sequencing the genomes of Pseudoalteromonas sp. Strain PLSV (13) and Alteromonas sp.…”
mentioning
confidence: 99%